Leiomoma Apoplektik : Morfologi Tidak Biasa dari Leiomioma yang Menyerupai Keganasan, Sebuah Laporan Kasus - Hamidiyah, Silpi (As-Shiha: Jurnal Kesehatan, 2024)
Apoplectic leiomyoma is a benign mesenchymal tumor originating from myometrial smooth muscle cells which undergoes hemorrhagic degeneration due to exposure to progesterone (progesterone analogues, contraceptive pills, pregnancy and postpartum). Not much attention has been paid to apoplectic leiomyomas, but it has wide morphological spectrum and often lead to diagnostic pitfalls, especially with malignancy. We report the case of 50-year-old woman with multiple uterine leiomyomas containing necrotic foci and central blood clots. The histopathological feature shows the presence of a zonation area, where the central area contains extensive necrosis and hemorrhage, rimmed by a peripheral area consisting of a proliferation of spindle-shaped smooth muscle cells with a cigar-like nucleus, fine chromatin, arranged in densely intersecting fascicles, between the two zones there is cells with degenerated nuclei, 8/10 HPF mitoses and intercellular edema. The theoretical approach regarding apoplectic leiomyoma is fundamental considering the morphological similarity of this tumor with leiomyosarcoma and smooth muscle tumors of uncertain malignant potential, which are the differential diagnosis of this neoplasia.